Custom-made computer-aided-design/ computer-assisted-manufacturing (CAD/CAM) synthetic bone grafts for alveolar ridge augmentation: A retrospective clinical study with 3 years of follow-up. (December 2022) - Mangano, Carlo; Luongo, Giuseppe; Luongo, Fabrizia; Lerner, Henriette; Margiani, Bidzina; Admakin, Oleg; Mangano, Francesco
Abstract: Purpose: To report on the results obtained with computer-aided-design/ computer-assisted-manufacturing (CAD/CAM) custom-made synthetic hydroxyapatite/beta-tricalcium-phosphate (HA/beta-TCP) bone grafts in alveolar ridge augmentation for dental implant placement. Methods: The procedure included: (1) cone-beam computed tomography (CBCT) of the bone defect; (2) virtual design of the custom-made onlay bone grafts; (3) milling of grafts from a pre-formed block of synthetic HA/beta-TCP; and (4) bone reconstructive surgery. Implants were placed 8 months later. The patients were followed for 3 years. The study outcomes were: (1) intra- and immediate post-operative complications; (2) 8-month vertical and horizontal bone gain; (3) implant survival; (4) implant-crown success; and (5) peri-implant marginal bone loss (MBL). Results: Twenty-six patients underwent ridge augmentation with custom-made CAD/CAM HA/beta-TCP onlay grafts. Eight months later, these patients were rehabilitated with dental implants. During surgery, 25/26 (96.1%) of the grafts adapted well to the bone defect. Immediate post-operative complications were pain and swelling (2/26 patients: 7.6%), and bone graft exposure (3/26: 11.5%); one exposure led to infection, removal of the graft, and failure of the procedure. Excellent integration of the other grafts was observed 8 months after the regenerative procedure, with mean vertical and horizontal bone gains of 2.10 mm (± 0.35) and 2.96 mm (± 0.45), respectively. Twenty-five implants were placed and restored with single crowns. Three years later, all implants were in function. The 3-year implant crown success rate and peri-implant MBL were 92.0% and 0.7 mm (±0.19), respectively. Conclusions: With custom-made CAD/CAM synthetic HA/beta-TCP onlay grafts reconstruction of small vertical and/or horizontal defects of the alveolar ridge was obtained; this enabled implant placement, with high implant-crown success rate after 3 years. Further studies are needed to validate this technique. Statement of Clinical Relevance: Custom-made CAD/CAM synthetic HA/beta-TCP onlay grafts may represent an option for regeneration of small bone defects prior to implant placement.